2009
DOI: 10.1074/jbc.m806893200
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Dual Oxidases Duox1 and Duox2

Abstract: Dual oxidases were initially identified as NADPH oxidases producing H 2 O 2 necessary for thyroid hormone biosynthesis. The crucial role of Duox2 has been demonstrated in patients suffering from partial iodide organification defect caused by biallelic mutations in the DUOX2 gene. However, the Duox1 function in thyroid remains elusive. We optimized a functional assay by co-expressing Duox1 or Duox2 with their respective maturation factors, DuoxA1 and DuoxA2, to compare their intrinsic enzymatic activities under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(53 citation statements)
references
References 50 publications
6
47
0
Order By: Relevance
“…7 It has been reported that H 2 O 2 production increases with increasing DUOX expression at the plasma membrane. 18 A model of bacterial killing at the airway epithelial cells is now considered that is similar to the killing mechanism of the NADPH oxidase in phagocytes. 19 …”
Section: Discussionmentioning
confidence: 99%
“…7 It has been reported that H 2 O 2 production increases with increasing DUOX expression at the plasma membrane. 18 A model of bacterial killing at the airway epithelial cells is now considered that is similar to the killing mechanism of the NADPH oxidase in phagocytes. 19 …”
Section: Discussionmentioning
confidence: 99%
“…[18] Thei ntracellular loop between transmembrane helix Ia nd II contains two Ca 2+ -binding EF-hand motifs,a nd calcium binding to DUOX2 enhances H 2 O 2 production. [19] TheN OX2-like domain of DUOXs contains one NADPH and one flavine adenine dinucleotide (FAD) binding site,a nd it retains the structural features of phagocyte NOX2 for effective electron transfer from NADPH to FADa sw ell as the Comp.I Ib inding of heme and molecular oxygen. [20] Interestingly,t he generation of H 2 O 2 by Comp.III DUOX2 does not depend on TSH, [21] but decreases as the concentration of iodide increases.…”
Section: Production Of Hydrogen Peroxide By Dual Oxidasesmentioning
confidence: 99%
“…Along the same lines, Laurindo and coworkers provide evidence for a possible regulatory association of Nox1, Nox2, Nox4 and p22 phox with protein disulfide isomerase, a redox chaperone and member of the thioredoxin family [166168]. Nox5 and Duox enzymes are activated by agonist-induced increases in intracellular calcium in concert with various phosphorylations [169]. Finally, H 2 O 2 is detected as the primary product from Duox1, Duox2 and Nox4 rather than O 2 •− as is the case with the other isoforms.…”
Section: Functional Distinctions Among Nox Isoforms: Heterodimerizmentioning
confidence: 99%